Case Report: Anaerococcus vaginalis spondylodiscitis diagnosed and cured based on nanopore targeted sequencing - Bing Zhou; Bing Zhou; Youfeng Guo; Beiduo Shen; Ziqi Zhu; Bin Yu; Gen Li; Ming Zong; Tao Hu; Tao Hu; Desheng Wu (Frontiers in Medicine, 2025)
Spondylodiscitis caused by Anaerococcus vaginalis has not been reported yet, making it worthy of further exploration. We closely monitored a patient who experienced worsened low back pain for 1 month and was unable to walk due to severe pain for 1 week. Through thorough examinations, the patient was diagnosed with lumbar disc herniation and a suspected case of spondylodiscitis, necessitating posterior lumbar surgery. All culture results returned negative. However, nanopore targeted sequencing (NTS) identified the presence of Anaerococcus vaginalis. Subsequent administration of appropriate antibiotics resulted in a favorable clinical outcome for the patient.